Heat-mediated reduction of apoptosis in UVB-damaged keratinocytes in vitro and in human skin ex vivo. Issue 1 (December 2016) - Calapre, Leslie; Gray, Elin; Kurdykowski, Sandrine; David, Anthony; Hart, Prue; Descargues, Pascal; Ziman, Mel
Abstract Background UV radiation induces significant DNA damage in keratinocytes and is a known risk factor for skin carcinogenesis. However, it has been reported previously that repeated and simultaneous exposure to UV and heat stress increases the rate of cutaneous tumour formation in mice. Since constant exposure to high temperatures and UV are often experienced in the environment, the effects of exposure to UV and heat needs to be clearly addressed in human epidermal cells. Methods In this study, we determined the effects of repeated UVB exposure 1 kJ/m2 followed by heat (39 °C) to human keratinocytes. Normal human ex vivo skin models and primary keratinocytes (NHEK) were exposed once a day to UVB and/or heat stress for four consecutive days. Cells were then assessed for changes in proliferation, apoptosis and gene expression at 2 days post-exposure, to determine the cumulative and persistent effects of UV and/or heat in skin keratinocytes. Results Using ex vivo skin models and primary keratinocytes in vitro, we showed that UVBplus heat treated keratinocytes exhibit persistent DNA damage, as observed with UVB alone. However, we found that apoptosis was significantly reduced in UVBplus heat treated samples. Immunohistochemical and whole genome transcription analysis showed that multiple UVBplus heat exposures induced inactivation of the p53-mediated stress response. Furthermore, we demonstrated that repeated exposure to UVplus heat induced SIRT1 expression and a decrease in acetylated p53 in keratinocytes, which is consistent with the significant downregulation of p53-regulated pro-apoptotic and DNA damage repair genes in these cells. Conclusion Our results suggest that UVB-induced p53-mediated cell cycle arrest and apoptosis are reduced in the presence of heat stress, leading to increased survival of DNA damaged cells. Thus, exposure to UVB and heat stress may act synergistically to allow survival of damaged cells, which could have implications for initiation skin carcinogenesis.